Immune modulatory roles of radioimmunotherapy: biological principles and clinical prospects - Wang, Xuefeng; Wang, Yu; Zhang, Yonggang; Shi, Hongyun; Liu, Kuan; Wang, Fang; Wang, Yue; Chen, Huijing; Shi, Yan; Wang, Ruiyao (Frontiers in Immunology, 2024)
Radiation therapy (RT) not only can directly kill tumor cells by causing DNA doublestrand break, but also exerts anti-tumor effects through modulating local and systemic immune responses. The immunomodulatory effects of RT are generally considered as a double-edged sword. On the one hand, RT effectively enhances the immunogenicity of tumor cells, triggers type I interferon response, induces immunogenic cell death to activate immune cell function, increases the release of proinflammatory factors, and reshapes the tumor immune microenvironment, thereby positively promoting anti-tumor immune responses. On the other hand, RT stimulates tumor cells to express immunosuppressive cytokines, upregulates the function of inhibitory immune cells, leads to lymphocytopenia and depletion of immune effector cells, and thus negatively suppresses immune responses.Nonetheless, it is notable that RT has promising abscopal effects and may achieve potent synergistic effects, especially when combined with immunotherapy in the daily clinical practice. This systematic review will provide a comprehensive profile of the latest research progress with respect to the immunomodulatory effects of RT, as well as the abscopal effect of radioimmunotherapy combinations, from the perspective of biological basis and clinical practice.